EFEKTIVITAS GAME WHO AM I DALAM MENINGKATKAN DAYA INGAT DAN PEMAHAMAN SISWA TERHADAP SEJARAH KEBUDAYAAN ISLAM DI MA UNGGULAN NUR AL JADID WARU, SIDOARJO - Alfi Akhsanul Haq; Nur Sa’adatut Daraini; Sholehuddin Sulaiman; Nizam Ramadhan (Al-Ihda' : Jurnal Pendidikan dan Pemikiran, 2025)
This research aims to investigate the effectiveness of the educational game Who Am I in improving students' memory and understanding of the subject of Islamic Cultural History (SKI) at MA Unggulan Nur Al Jadid, Waru, Sidoarjo. The approach method uses a qualitative case study, and 15 eleventh-grade students who have difficulty understanding Islamic Cultural History (SKI) material were made the subjects of the research. Data were obtained through observation, interviews, tests, and documentation. Learning was conducted in two cycles using the Who Am I game designed to identify figures of Islamic reform and their ideas. The research results show that the implementation of the Who Am I game significantly improved students' memory and understanding. The enthusiasm and participation of students in the learning process increased, as evidenced by the rise in participation and better test results in each cycle. The elements of competition and challenge in the game have proven effective in motivating students to learn more deeply. Thus, the game Who Am I can be used as an enjoyable and effective alternative learning method to enhance the quality of SKI education.